2015
DOI: 10.1589/jpts.27.1691
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical health status and quality of life among Saudi older adults

Abstract: [Purpose] This study investigated physical health status and quality of life among older Saudi adults. [Subjects and Methods] Participants included older adults (N = 55) aged 60–90 years (mean = 67.9± 7.71) from a major hospital in Jeddah. Subjects completed surveys and evaluations including assessments of personal and socio-demographic characteristics, caregiver presence, personal habits, perceived health, primary physical and psychological complaints, physician-diagnosed chronic diseases, and functional capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
18
2
Order By: Relevance
“…Aging has been identified as a key factor for T2DM [4,25,26] and impaired HRQoL [12,15,35,36]. Therefore, it is expected a negative association between age and HRQoL among patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Aging has been identified as a key factor for T2DM [4,25,26] and impaired HRQoL [12,15,35,36]. Therefore, it is expected a negative association between age and HRQoL among patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly increased risk of falling has been seen in elderly persons with diabetes and hypertension. 6 The risk is also significantly increased in those with lower limb weakness, balance/gait problems, dizziness and visual disorders. 7 8 Education plays a big role in preventing or decreasing the incidence of falls, especially among elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Pain was present at more than 1 location in 45.4% of the subjects, with the most frequent sites being the limbs and/or joints. In addition, about 30% of the participants felt sad or very sad, 29.3% felt anxious or very anxious, 24.4% had been on sick leave because of their pain at least once in the preceding year, 12% had left or lost their job because of their pain during that period, and 47.2% considered that their pain affected their families or their relationships with friends (26.3%; see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Older age was associated with greater limitations, as expected. Several studies carried out in older people have shown considerable ADL problems in these subjects, and have explained that single sensory impairments (either visual or auditory) are significantly and independently linked with a high risk for depression and decreased self‐sufficiency in ADLs, which can adversely affect mobility and the ability to perform ADLs . Furthermore, it seems reasonable to think that the physiological deterioration due to age can be increased or accelerated by the presence of pain that, on many occasions, is due to the musculoskeletal pathology that frequently affects this population …”
Section: Discussionmentioning
confidence: 99%